The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1089/end.2016.0825
|View full text |Cite
|
Sign up to set email alerts
|

Primary SWL Is an Efficient and Cost-Effective Treatment for Lower Pole Renal Stones Between 10 and 20 mm in Size: A Large Single Center Study

Abstract: SWL is both an efficacious and cost-effective primary treatment for patients with solitary LP stones (10-20 mm). The majority of patients can be effectively treated with primary SWL in a dedicated stone center, with the benefits of a short length of stay, low complication, and auxiliary treatment rates. The referral of such patients to high-volume lithotripsy centers with demonstrable outcomes should be given due consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…There were 12 studies examining the cost of URS vs. SWL [ 11 22 ]. These took place in the USA [ 11 , 12 , 20 , 21 ], China, [ 13 15 , 19 ], Egypt [ 16 ], Taiwan [ 17 ] and the UK [ 18 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 12 studies examining the cost of URS vs. SWL [ 11 22 ]. These took place in the USA [ 11 , 12 , 20 , 21 ], China, [ 13 15 , 19 ], Egypt [ 16 ], Taiwan [ 17 ] and the UK [ 18 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 12 studies examining the cost of URS vs. SWL [ 11 22 ]. These took place in the USA [ 11 , 12 , 20 , 21 ], China, [ 13 15 , 19 ], Egypt [ 16 ], Taiwan [ 17 ] and the UK [ 18 , 22 ]. Seven of the included studies were retrospective cohort studies [ 12 14 , 18 21 ] two were prospective cohort studies [ 17 , 22 ] and the remaining three [ 11 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Chan et al demonstrated that SWL was an excellent choice for rapid and non-invasive treatment of solitary lower pole stones between 10-20 mm. 2 The efficacy and fiscal efficiency for the treatment of smaller (1-10 mm) had previously been demonstrated. 3,4 There remain a number of stones that are not suitable for treatment with SWL.…”
Section: Introductionmentioning
confidence: 99%